Freedom of Contract in Commercial Agreements: A Civil Law Analysis of Modern Business Practices - Wahyono, Wahyono; Dewanto, Wishnu; Kusuma, Tiyar Cahya; Anggawira, Anggawira (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2026)
Freedom of contract constitutes a fundamental principle in civil law, serving as the primary foundation for the creation and enforcement of commercial agreements. In contemporary business practices, this principle provides flexibility for parties to determine the content, structure, and mechanisms of their contractual relationships in accordance with their economic interests. However, the rapid development of modern commerce, including the expansion of standardized contracts and electronic transactions, has raised critical questions regarding the extent to which freedom of contract truly reflects equality and fairness between contracting parties. This study aims to analyze the position of the principle of freedom of contract within the civil law system and to examine its application and limitations in modern commercial agreements. Employing a normative legal research method with statutory and conceptual approaches, this research analyzes primary and secondary legal materials qualitatively. The findings indicate that freedom of contract remains a central pillar of civil law, but its implementation is inherently limited by mandatory legal provisions, public order, morality, and the principle of good faith. In modern business contexts, these limitations function as essential safeguards to maintain contractual balance and legal certainty. Therefore, the relevance of freedom of contract depends on its harmonious integration with principles of fairness and proportionality in commercial practice.